Gerakan Komunitas Sambatan Jogja (SONJO): Penyelenggaraan Perlindungan Sosial Informal Pada Masa Pandemi COVID-19 - Arintyas, Ameylia Puspita Rosa Dyah Ayu (Riau Journal of Empowerment, 2024)
The COVID-19 pandemic has changed various sectors, such as the economy, health and education, which has resulted in problems stemming from the hindrances in the activities of the three sectors. Even though it was over, the problems formed during that period remain and require an integrative solution. The government is primarily responsible for overcoming it, but during the pandemic, many grassroots collective works have emerged which have significantly overcome societal problems. One of the forms of this grassroots work is the Sbatan Jogja (SONJO) community. SONJO is a multi-actor movement that, during the pandemic, moved massively to organise informal social protection to reduce social risks due to economic, health and education problems. This research will focus on this issue using a qualitative case study method. Data was obtained based on interviews with SONJO initiators. The results obtained were that SONJO was an intermediary actor in the distribution of informal social protection during the COVID-19 pandemic in DI Yogyakarta.